Implementation of Inclusive Education Policies in Primary Schools: Islamic Perspectives in Comparative Studies Between Indonesia and Developed Countries - Yati, May; Sriyati,; Hatib, Fahmi (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study aims to systematically analyze the literature related to the implementation of inclusive education policies in primary schools from an Islamic perspective: a comparative study between Indonesia and other countries, as well as conduct a comparative study with best practices in developed countries, to explore the factors that support the success of inclusive education in these countries. Thus, this study will not only describe the current situation but also contribute to improving the quality of inclusive education at the primary school level in Indonesia. This study is a Systematic Literature Review (SLR) research using bibliometric analysis, the researcher conducted a visualization using VOSviewer software with co-occurrence analysis to describe the study of the critical thinking ability of elementary school students. Based on the results of a systematic literature review of 42 articles on the implementation of inclusive education policies in elementary schools both in Indonesia and in developed countries, 4 clusters identified four main interrelated themes: handling specific learning disorders, handling autism, education policies, and social aspects of inclusive education. Key challenges include system integration difficulties, resource limitations, and digital competency gaps while supporting factors include comprehensive policies, ongoing professional development, and structured support systems. The study concludes that the successful implementation of inclusive education policies requires a contextual approach that considers the unique challenges and potentials of each country, supported by multi-stakeholder collaboration, continuous professional development, and comprehensive policies, with recommendations for strengthening adaptive policies, developing sustainable teacher training programs, and continuing research on the impact of inclusive policies.